The Relationship Between Knowledge and the Utilization of the Maternal and Child Health (MCH) Book Among Pregnant Women at Tanjung Rejo Public Health Center, Deli Serdang Regency - Rahmat Jody Hamonangan Sihombing; Khairani Sukatendel; Deske Muhadi Rangkuti; Evita Mayasari; Miranda Olivia Hasiana Siburian (Green Publisher Indonesia, 2025)
Maternal Mortality (MMR) is still a global health problem that needs serious attention. In 2022, Deli Serdang Regency was recorded to have the highest AKI in North Sumatra Province, which was 16 per 42,363 live births. One of the efforts that can be made to reduce this number is by using the Maternal and Child Health Book (KIA). This study aims to analyze the relationship between the level of knowledge of pregnant women and the use of KIA books at the Tanjung Rejo Health Center, Deli Serdang Regency. This study uses an analytical observational design with a cross-sectional approach. A total of 100 pregnant women became respondents to the study. Data was collected through questionnaires, then analyzed using the Spearman statistical test. The use of KIA books is assessed through indicators of readability, comprehension, and application of information, while mother's knowledge is measured through the level of mastery of the content of KIA books. The results showed that the majority of pregnant women were at healthy reproductive age (55%), poorly educated (72%), unemployed (89%), and had high parity (56%). Most respondents (73%) fall into the category of poor utilization of KIA books, while 79% have a low level of knowledge. Statistical analysis showed a significant relationship between the level of knowledge of pregnant women and the use of KIA books (p = 0.001). The use of KIA books in pregnant women is significantly influenced by the level of knowledge.